Institutional, Cultural and Transaction Cost Influences on Entry Mode Choice and Performance - Brouthers, Keith D. (Journal of International Business Studies, 2002)
In this study, we examine foreign market entry mode choice and firm performance for a sample of European Union firms. Examining both financial and non-financial performance measures, we attempt to determine if firms that select their entry mode based on transaction cost, institutional context, and cultural context variables perform better than firms that make other mode choices. We found that mode choice did matter. Firms whose mode choice could be predicted by the extended transaction cost model performed significantly better, on both financial and non-financial measures, than did firms whose mode choice could not be predicted by the extended transaction cost model. Implications for future research are discussed.